Sosialisasi Pembuatan Sabun Cuci dari Limbah Minyak Goreng Bekas bagi Ibu-Ibu PKK - Erina Rulianti; Nisa Nurhidayanti; Isyulianto Isyulianto; Ika Juhriati; Dhonny Suwazan (Jurnal Nusantara Mengabdi, 2023)
Purpose: This service activity aims to provide new insights and knowledge for Jayamukti villagers, especially housewives in processing used cooking oil waste into laundry soap so that it is not disposed of directly and pollutes the environment. Methodology: This service activity includes four stages, namely planning, coordination, socialization of making laundry soap, evaluation of the results of the service. The results of the questionnaire were analyzed using Microsoft Excel to calculate the percentage of participant satisfaction Results: The results of the community service activities show that 85.71% of residents are very interested in washing soap from used cooking oil, as much as 91.43% of residents will collect used cooking oil and make laundry soap from used cooking oil, as much as 74.29% of residents are interested in innovating so they can selling washing soap from used cooking oil and as many as 85.71% of residents stated that they were satisfied with the socialization and mentoring activities for making laundry soap from used cooking oil that had been carried out. This shows that the service activities that have been carried out are very beneficial for residents, especially PKK women because they can create productive activities that can increase income. Conclusion: The socialization activities that have been carried out are very beneficial for residents, especially PKK women because they can create productive activities that can increase income. This is shown by the high interest of residents in being able to collect used cooking oil and process it into laundry soap and are very interested in innovating so they can sell washing soap from used cooking oil.